Improving Social Studies Learning Outcomes by Using Learning Video Media For Fourth Grade Students Of SDTQ Al Abidin Surakarta For The 2018/2019 Academic Year - Hartatik, Wiwik (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The research was motivated by the problem of the low social studies learning outcomes of fourth grade students. This is because teachers often use the lecture method, students only listen and record all information from the teacher. This study aims to explain whether the use of instructional video media in social studies subjects for class IV SDTQ Al Abidin Surakarta is able to improve student learning outcomes. This PTK consists of 2 cycles. Data collection techniques from learning outcomes tests at the end of each cycle meeting. The results showed an increase in student learning outcomes for social studies lessons. In the initial conditions, student learning outcomes complete KKM 15%. In the first cycle, the students who completed the KKM were 50%. The number of students who completed the KKM in the second cycle increased to 85%. There was an increase in the number of students who completed the KKM each cycle. With the evidence in this study, learning with video media is recommended to be applied in learning activities, in an effort to provide quality learning and can improve student learning outcomes.